Тарантул: повесть / Г. И. Матвеев ; худ. Н. Кочергин - Матвеев Герман (Школьная библиотека, 2010)
5-7 кл. Экземпляры: ф.4 (20131204) / Инвентарный номер: 55768 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: М 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44